Pendampingan Dan Pengembangan Wirausaha Pemula Bagi Komunitas Pemuda dan Wanita di Sidoarjo: Pendampingan dan Pengembangan Wirausaha Pemula bagi Komunitas Pemuda dan Wanita di Sidoarjo - Monica Adjeng Erwita; Marliana Junaedi; Veronika Rahmawati; Deatri Arumsari Agung (Universitas Muhammadiyah Palembang, 2025)
The purpose of this community service activity is to inspire and motivate young people and women's groups to become entrepreneurs in the digital era, and to help them find creative ideas to design businesses that make maximum use of current information technology. The target of this activity is 23 young people and housewives with their respective frozen food products, namely meatballs, siomay, and chicken nuggets. The location of the activity was carried out in Semambung Village, Gedangan District, Sidoarjo, East Java. The community service team used a method that was divided into several stages, namely (1) Provision dan Training, (2) Discussion, Q and A (3) Production dan Sales Practice, and (4) Evaluation, through 1 online session and 7 offline sessions. This activity has had an economic impact, namely increased income, understanding of financial management, product development, and expansion opportunities. In addition to the economic impact, this activity also has a social impact, namely skills development, increased community spirit, and empowerment of young people and women's groups. Several challenges such as limited space, production facilities, and mastery of digital marketing techniques still require further attention to support the sustainability of this program.